Leading Commodities of Livestock Subsector in Riau Islands Province - Ahmad Misbah; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Agro Ekonomi, 2018)
This study aims to determine the leading commodities of livestock subsector in Riau Islands Province and to find out its growth structure. Location quotient (LQ), dynamic location quotient (DLQ), Klassen Typology (KT) and shift-share analysis (SSA) were applied in the analysis. The results at the subsector level shows that livestock becomes the leading subsector of agriculture in Riau Islands Province. At the commodity level, the livestock commodities used as research objects are selected based on relatively dominant production in Riau Islands Province, so it is expected to meet the representation in subsector. The selected commodities are: pig, broiler, cattle, goat, duck and egg of layer chicken. Pigs are the leading commodity in the livestock subsector in the Riau Islands Province. The growth structure of the livestock subsector is entirely positive in the economy. Livestock subsector has become the biggest contributor of GDP growth in agriculture sector in Riau Islands Province. All growth components of this subsector are positive and categorized in quadrant I (rapid growth) Klassen Typology. Likewise at the commodity level, the growth structure of leading commodities (pigs) are the same as the subsector level.